Facile Rapid Synthesis of Polyaniline (PANI) Nanofibers - Sachin S. Sawant; Ashok D. Bhagwat; Chandrashekhar M. Mahajan (Журнал нано- та електронної фізики)
A Polyaniline (PANI) nanofibers have been successfully synthesized by a facile rapid oxidative polymerization of aniline hydrochloride and ammonium persulfate at high temperature (60 C). The structural and optical properties of PANI nanofibers are investigated by using X-ray diffraction (XRD), UV-VIS Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). The XRD analysis ascertains formation of PANI with nanocrystalline nature with average crystallite size 30 nm. Further, FTIR pattern confirmed the formation of PANI. SEM analysis has revealed homogeneous fibrous morphology of PANI nanofibers, a well formed mesh of interconnected and entangled PANI nano-fibers over the scanned area. The UV-VIS spectroscopic analysis shows three major absorption peaks at 256.73, 361.17 and 480.95 nm confirmed the PANI formation with conducting state.